1993
DOI: 10.1002/anie.199305761
|View full text |Cite
|
Sign up to set email alerts
|

[Tc6X8] Clusters in ternary Technetium Chalcogenides

Abstract: Almost regular Tc6 octahedrons inside cubes constructed of chalcogen atoms X (X = S, Se) form the characteristic structural element in ternary alkali metal technetium chalcogenides. The Tc6X8 units are linked through X or X2 bridges (in the picture on the right the bridging X atoms are included with the central unit) to give three‐dimensional frameworks, and the alkali metal ions are inserted into suitable interstices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Only selected cluster phases are reported here to highlight the relationship between the halides and chalcogenides, since numerous reviews discuss such cluster phases. [99][100][101][102][103][104] Two basic cluster units are observed consisting of either an M 6 X 8 core in which the ligands cap the faces of the octahedral cluster, or with an M 6 X 12 core where the ligands bridge the edges of the cluster (Figure 7). [99][100][101][102][103][104] In both cases, these bridging ligands are designated as inner ligands, X i .…”
Section: Construction Of Complex Halide/chalcogenide Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…Only selected cluster phases are reported here to highlight the relationship between the halides and chalcogenides, since numerous reviews discuss such cluster phases. [99][100][101][102][103][104] Two basic cluster units are observed consisting of either an M 6 X 8 core in which the ligands cap the faces of the octahedral cluster, or with an M 6 X 12 core where the ligands bridge the edges of the cluster (Figure 7). [99][100][101][102][103][104] In both cases, these bridging ligands are designated as inner ligands, X i .…”
Section: Construction Of Complex Halide/chalcogenide Analoguesmentioning
confidence: 99%
“…[99][100][101][102][103][104] Two basic cluster units are observed consisting of either an M 6 X 8 core in which the ligands cap the faces of the octahedral cluster, or with an M 6 X 12 core where the ligands bridge the edges of the cluster (Figure 7). [99][100][101][102][103][104] In both cases, these bridging ligands are designated as inner ligands, X i . Six terminal ligands attach to each type of cluster in apical positions and are designated as outer ligands, X a .…”
Section: Construction Of Complex Halide/chalcogenide Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Se, x = 12-13), were firstly reported by Bronger et al [16,17] Kryutchkov et al reported a bromide-capped cluster [Tc 6 (µ 3 -Br) 5 Br 6 ] 2-in which the eight capping sites were not fully occupied. [18][19][20] In this study, we report on several new chalcogenide-capped hexatechnetium(III) complexes that are expected to be the precursors for the synthesis of various hexatechnetium(III) complexes.…”
Section: Introductionmentioning
confidence: 67%